Macroeconomic determinants of economic growth. An international perspective - Yashasvi PANDEY; C.R. BISHNOI (Theoretical and Applied Economics, 2023)

(untitled)
The objective of this study is to analyse the effect of selected macroeconomic determinants on economic growth of 40 countries taken 10 each from four income groups of countries as classified by World Bank – low income, lower-middle income, upper-middle income and high income group for the time period 2000-2019 by estimating two panel growth models – the basic growth model and the extended growth model. In the basic growth model, only five real factors affecting economic growth have been considered, namely, private consumption expenditure, capital formation, government expenditure, exports and imports and in the extended growth model, additional factorsinflation rate, FDI inflows and population growth have been also included to obtain a more detailed analysis of the various determinants of economic growth. Separate panel growth models are estimated for all four income groups as well as taking all data as a whole by three conventional methods (POLS, FEM and REM) of panel model. After estimating models, diagnostic tests were conducted to check the problems of cross-section dependence, heteroscedasticity and autocorrelation. To correct these problems PCSE/FGLS model was used, depending upon the number of cross-sectional units and number of time periods. The estimated final model suggests that capital formation and FDI inflows have positive significant impact on economic growth, whereas government spending significantly negatively impacts economic growth. Private consumption expenditure also plays a significant role in positively affecting growth rate for low income as well as high income group. Thus, countries should focus on capital formation and developing a more conducive environment for promotion of domestic as well as foreign investment.